2022
DOI: 10.1038/s41598-022-26113-1
|View full text |Cite
|
Sign up to set email alerts
|

Impairment in novelty-promoted memory via behavioral tagging and capture before apparent memory loss in a knock-in model of Alzheimer’s disease

Abstract: Alzheimer’s disease (AD) is associated with cognitive impairments and age-dependent memory deficits which have been studied using genetic models of AD. Whether the processes for modulating memory persistence are more vulnerable to the influence of amyloid pathology than the encoding and consolidation of the memory remains unclear. Here, we investigated whether early amyloid pathology would affect peri-learning novelty in promoting memory, through a process called behavioral tagging and capture (BTC). AppNL-G-F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 84 publications
1
5
0
Order By: Relevance
“…These deficits were abolished by perinatal choline supplementation at early ages (3 and 6 months) but not at the later age (12 months) suggesting that choline supplementation is able to prevent early spatial learning deficits that are found in App NL-G-F mice. Previous results of App NL-G-F mice in the Barnes Maze have varied [ 24 , 29 , 30 ]. One study that used male and female 6–9-month-old mice, also found a significant increase in latency to reach the target hole in App NL-G-F mice compared to wildtype mice [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These deficits were abolished by perinatal choline supplementation at early ages (3 and 6 months) but not at the later age (12 months) suggesting that choline supplementation is able to prevent early spatial learning deficits that are found in App NL-G-F mice. Previous results of App NL-G-F mice in the Barnes Maze have varied [ 24 , 29 , 30 ]. One study that used male and female 6–9-month-old mice, also found a significant increase in latency to reach the target hole in App NL-G-F mice compared to wildtype mice [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous results of App NL-G-F mice in the Barnes Maze have varied [ 24 , 29 , 30 ]. One study that used male and female 6–9-month-old mice, also found a significant increase in latency to reach the target hole in App NL-G-F mice compared to wildtype mice [ 29 ]. Another study that used 6-month-old mice with 9 training days for their trial phase found no difference in latency to reach the target hole between wildtype and App NL-G-F mice [ 30 ] and another study found only deficits in App NL-G-F mice as compared to wildtype mice, in the trial phase of the Barnes Maze at 8 months of age but not at 4 or 6 months of age [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Prior lifelong wheel running improves long-term memory in a brief water maze test at old age and increases signal intensities in genes associated with synaptic transmission and energy metabolism [ 82 ]. Activities in prior training in this or our earlier studies [ 15 , 26 , 83 ] are relatively mild, compared to intensive exercise that is shown to improve learning or memory (e.g., wheel running for 1.5 km per day in [ 82 ] or treadmill running for approximately 330 m per day for 100 days in [ 84 ]). Environmental enrichment has also been shown to improve cognition in aging, although it typically involves more objects for prolonged interaction [ 85 87 ] than two landmarks and sandwells in this study that animals tend to habituate to.…”
Section: Discussionmentioning
confidence: 99%
“…It is conceivable that cognitive stimulation plays a crucial role in the prior training effect seen here. The stimulation includes learning of the procedural aspects of the task as discussed above, formation and consolidation of the spatial map that enables assimilation in the case of schema learning [ 88 , 89 ], rapid updating and maintaining of daily information on reward locations, and occasional exposure to novelty that modulated memory persistence [ 15 , 18 , 26 , 30 , 83 ]. Studies have shown that ‘training’, as opposed to activity-only control, is critical for improvement in navigation or memory abilities in aging [ 90 , 91 ].…”
Section: Discussionmentioning
confidence: 99%
“…Metaplastic processes could be used towards ameliorating AD-related plasticity and STC impairments, and this has been demonstrated using RYR-priming to re-establish late-LTP and STC in APP/PS1 mice [164]. The lack of associativity in AD has also been demonstrated behaviourally, with loss of novelty-induced priming occurring before memory loss [175].…”
Section: Stc In Pathologiesmentioning
confidence: 99%